2016
DOI: 10.1021/jacs.6b07440
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the Constitutive, Homodimeric Protein–Protein Interface in CK2β Using a Biophysical Fragment-Based Approach

Abstract: Identifying small molecules that induce the disruption of constitutive protein–protein interfaces is a challenging objective. Here, a targeted biophysical screening cascade was employed to specifically identify small molecules that could disrupt the constitutive, homodimeric protein–protein interface within CK2β. This approach could potentially be applied to achieve subunit disassembly of other homo-oligomeric proteins as a means of modulating protein function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…Indeed, the L86A/L87A substitution reduced binding to GST-UL44 in pulldown assays (Figure 1A), and greatly reduced protein stability in TSA (Figure 1B). The latter observation is consistent with the fact that shown that substitutions affecting protein multimerization decrease the Tm (41). Similarly, the L86A/L87A substitution reduced FRET efficiency and the B 50 value for UL44 self-interaction, but had little or no effect on the ability of the protein to bind to its catalytic subunit UL54 (Figures 2 and 3), therefore suggesting that the protein was still properly folded.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, the L86A/L87A substitution reduced binding to GST-UL44 in pulldown assays (Figure 1A), and greatly reduced protein stability in TSA (Figure 1B). The latter observation is consistent with the fact that shown that substitutions affecting protein multimerization decrease the Tm (41). Similarly, the L86A/L87A substitution reduced FRET efficiency and the B 50 value for UL44 self-interaction, but had little or no effect on the ability of the protein to bind to its catalytic subunit UL54 (Figures 2 and 3), therefore suggesting that the protein was still properly folded.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the fraction of His 6 -UL44-L86A/L87A pulled down was clearly reduced, indicating impaired ability to associate with GST-UL44, and thus further supporting the validity of the previously published crystal structure (Figure 2A, right panel ). Since single amino acids substitutions impairing self-association of multimeric proteins are known to decrease protein stability (41), we decided to further corroborate our findings by comparing the stability of His 6 -UL44 and its L86A/L87A derivative by thermal shift assays (TSAs). To this end, we initially performed a small-scale screening to identify the most suitable conditions to assess UL44 stability by TSA (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…However, small-molecule inhibitors have been shown to cause negative shifts in the Tm values of target proteins by disrupting their oligomeric interfaces, leading to thermal destabilization and subsequent loss of interaction between the protein subunits (23,24). Some examples include 6hydroxy-DL-dopa binding to RAD52 (25) and SPD304 binding to TNF-α (26).…”
Section: Mechanism Of Action Of Tfq Against Sars-cov-2 M Promentioning
confidence: 99%
“…3, a-c). Because compounds were initially selected for their capacity to occupy preferential sites on the dimerization interface of p8, the decrease in T m values suggests that these four fragments would destabilize the homodimeric state (19). To complete the validation stage, we next employed the saturation transfer difference NMR (STD-NMR) approach (20).…”
Section: Two Fragments Turned Out To Destabilize the Dimerization Intmentioning
confidence: 99%